2013
DOI: 10.1007/s00299-013-1550-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of the involvement of heat shock protein 90 in brassinosteroid signaling in Arabidopsis T87 cultured cells

Abstract: Heat shock protein 90 (HSP90) is a highly conserved molecular chaperone that is reportedly involved in the proper folding, stabilization, intracellular trafficking, maintenance and degradation of numerous proteins, as well as the facilitation of cellular signaling in various organisms including plants. Brassinosteroids (BRs), a class of unique steroidal hormones, play crucial roles in plant growth and development. The interaction between HSP90 proteins and BR action has been poorly understood. Here, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Recently, Samakovli et al (2014) reported that HSP90 interacts with a BR signaling component, BIN2 kinase, to modulate its nuclear retention. Independently of their study, HSP90 was also found to bind to BES1 (Lachowiec et al, 2013;Shigeta et al, 2014). These findings suggest the involvement and importance of HSP90 activity in BR signaling.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, Samakovli et al (2014) reported that HSP90 interacts with a BR signaling component, BIN2 kinase, to modulate its nuclear retention. Independently of their study, HSP90 was also found to bind to BES1 (Lachowiec et al, 2013;Shigeta et al, 2014). These findings suggest the involvement and importance of HSP90 activity in BR signaling.…”
Section: Introductionmentioning
confidence: 88%
“…Template DNA of BRASSINAZOLE RESISTANT 1 (BZR1) and HSP90.3 for in vitro transcription was constructed similarly to that of BRASSINOSTEROID INSENSITIVE 1-EMS-SUPRESSOR 1 (BES1) described in Shigeta et al (2014). The templates of truncated BES1 were constructed from its full-length cDNA (pEU-E01-HF-BES1) using the PrimeSTAR Mutagenesis Basal Kit (TaKaRa Bio Inc., Shiga, Japan).…”
Section: In Vitro Transcription Linked Cell-free Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Important to note that genes coding these chaperones are greatly induced by BRs directly under heat shock, and level of protein products is increased after heat shock (Dhaubhadel et al 2002). Recently, a new evidence was found about role of HSPs, particularly HSP90, in brassinosteroids signaling in Arabidopsis cells (Shigeta et al 2014). It has been shown that Electronic supplementary material The online version of this article (doi:10.1007/s10725-015-0093-3) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, inhibitor of HSP90 ATPase activity-geldanamycin-suppressed BR-induced downregulation of key biosynthesis genes-CONSTITUTIVE PHOTHOMOR-PHOGENESIS AND DWARFISM (CPD) and DWARF4 in vivo (Shigeta et al 2014). HSP90 also assists nuclear localization of BRs signaling component-BIN2 (BRAS-SINOSTEROID INSENSITIVE 2) protein and geldanamycin treatment force BIN2 translocation to cytosol (Samakovli et al 2014).…”
Section: Introductionmentioning
confidence: 98%